Factors Affecting Stock Price and Firm Value as Intervening Variable: The Case of Consumer Sector Firm-Listed at Indonesian Stock Exchange - Amanda, Widya Ayu; Fatimah, Fatimah; Chairiyah, choriyah (International Journal of Finance Research, 2024)
The object of this research is primary consumer sector companies registered on the IDX, where the data is in the form of financial reports for the 2019-2023 period. The research method that is appropriate for this research is associative research because the author wants to know the influence of the Current Ratio, debt-to-asset ratio, and Net Profit Margin variables on stock prices with company value as an intervening variable. In this research, the operational variable is the stock price. (Z) as the dependent variable, company value (Y) as the intervening variable, while the independent variables are Current Ratio (X1), Debt to Asset Ratio (X2), and Net Profit Margin (X3). The indicators for share prices are closing prices; company value is price to book value; current ratio is current assets and current liabilities; debt to asset ratio is total debt and total assets; net profit is profit after taxes and sales. Based on the criteria for determining the sample size, 59 primary consumer sector companies meet these criteria.  The following conclusions can be obtained: 1. The Current Ratio and net profit margin have a negative and insignificant effect on company value; 2. The Debt-to-Asset Ratio positively and significantly affects company value; 3. Net Profit Margin has a negative and insignificant effect on company value; 4. The Current Ratio has a positive but insignificant effect on share prices; 5. The Debt-to-Asset Ratio negatively and significantly affects share prices; 6. Net Profit Margin has a negative and insignificant effect on share prices, 7. Company value has a positive and significant effect on share prices